AUTOMATIC WATERING SYSTEM FOR ANTHURIUM PLANTS POWERED BY A 10 WP SOLAR PANEL - Silvia Maharani; Erma Triawati Christina; Ganjar Febriyani Pratiwi (TESLA: Jurnal Teknik Elektro, 2025)
Anthurium plants are sensitive to soil moisture levels, so a decrease in humidity can disrupt their health and cause the leaves to wilt quickly and die. Manual watering is considered ineffective, especially when the owner is not at home or there is a power outage. Therefore, an independent automatic watering system is needed that utilizes renewable energy using a 10 Wp solar panel. This system consists of a V2.0 soil moisture sensor to detect soil moisture, a DHT22 sensor to detect the temperature around the anthurium plant environment, a relay module as an automatic switch, a DC pump for the plant watering actuator, a buzzer as an audible indicator when the plant is dry, a DFPlayer Mini as a sound module that plays “Anthurium Needs Watering,” and an OLED display that shows soil moisture and temperature information around the anthurium plant, and uses a 12 V 8 Ah battery controlled by SCC. Test results show that the panel is capable of producing a maximum power of 10.21W with an output voltage of 17.9 V and a current of 0.57 A. The charging process for a 12 V 8 Ah battery for 4 hours shows a gradual increase in voltage from 12.73 V to 13.85 V. The automatic watering system activates when soil moisture is < 47%, indicating that the soil is dry. The automatic watering system activates the DC pump to water the plants, accompanied by audio information from the buzzer and mini DFPlayer. When soil moisture is ≥ 47%, indicating that the soil is wet, the water pump, buzzer, and mini DFPlayer automatically stop when the soil moisture is sufficient Abstrak Tanaman anthurium tergolong sensitif terhadap kadar air tanah, sehingga penurunan kelembapan dapat mengganggu kesehatannya dan menyebabkan daun cepat layu hingga mati. Penyiraman secara manual dinilai kurang efektif, terutama saat pemilik tidak berada di tempat atau terjadi pemadaman listrik. Oleh karena itu, diperlukan sistem penyiraman otomatis yang mandiri dengan memanfaatkan energi baru terbarukan dengan menggunakan panel surya 10 Wp. Sistem ini terdiri dari sensor kelembapan tanah V2.0 untuk mendeteksi kelembapan tanah, sensor DHT22 untuk mendeteksi suhu di sekitar lingkungan tanaman anthurium, modul relay sebagai sakelar otomatis, pompa DC untuk aktuator penyiram tanaman, buzzer sebagai indikator bunyi ketika tanaman dalam keadaan kering, DFPlayer Mini sebagai modul pemutar suara berupa “Anthurium Butuh Disiram”, dan OLED display menampilkan informasi kelembapan tanah dan suhu sekitar tanaman anthurium, serta menggunakan baterai 12 V 8 Ah yang dikontrol oleh SCC. Hasil pengujian menunjukkan panel mampu menghasilkan daya maksimum sebesar 10,21W dengan tegangan output mencapai 17,9 V dan arus 0,57 A. Proses pengisian daya pada aki 12 V 8 Ah selama 4 jam menunjukkan peningkatan tegangan secara bertahap dari 12,73 V hingga mencapai 13,85 V. Sistem penyiram otomatis aktif ketika kelembapan tanah < 47% yang menunjukkan kondisi tanah dalam keadaan kering, sistem penyiraman otomatis mengaktifkan pompa DC untuk menyiram tanaman, disertai informasi suara dari buzzer dan Dfplayer mini. Ketika kelembapan tanah ≥ 47% yang mendeteksi tanah dalam kondisi basah, maka pompa air, buzzer, DFPlayer mini berhenti secara otomatis saat kelembapan tanah tercukupi